Hydrogenation of Palm Fatty Acid Distillate (PFAD) for Food Additive Raw Material - Ravi Zakaria, Abdu
Rafination process of CPO produce palm fatty acid distilate (PFAD) as a by product which contain 82-99 % of free fatty acid (FFA). PFAD can be used as a raw material to produce food additives like stearic acid and magnesium stearate. The problem is stearate content in PFAD can’t meet the commercial specifiation, so that we need the hydrogenation of PFAD to increase the stearate fraction in PFAD. Therefore, this research is intend to study the hydrogenation reaction of PFAD. The research was held by three stages. The first stage was mean to compare hydrogenation methode for PFAD between Gaseous Hydrogenation (GH) and Catalytic Transfer Hydrogenation (CTH). The second stage was mean to determine the effect of process parameter in selected hydrogenation methode. The third stage was mean to scale-up the hydrogenation process. CTH methode use ammonium format as a hydrogen donor compound and 10% Pd/C as catalyst, meanwhile GH methode use gaseous hydrogen and catalyst 19% Ni/Al2O3. Based on the research, CTH product is more preferable rather than GH product, CTH product has lower iodin value which mean the hydrogenation conversion was higher as well as from visual-sensoric observation the product is more like to stearic acid, so the CTH was selected as a hydrogenation methode for the next stage of research. The challenge of CTH is it separation process of product and catalyst which much harder than GH. In 70, 80, and 90?C temperatur variation of CTH it is known that increasing temperature can increase the saturation index of fatty acid. In 2,3 M ; 3,6 M ; and 4,2 M ammonium formate concentration variation is known that 3,6 M concentration has a highest saturation index. On the Third stage with used of 30 g PFAD, the yield of hydrogenated product is higher than the regular which used only 10,8 g PFAD/batch.